Pengaruh Influencer dan Fear of Missing Out (FOMO) Terhadap Minat Beli Produk Fashion UMKM di Kabupaten Sidenreng Rappang - Alifia Zahra Syahril; Nurfadhilah Nurfadhilah; Muzdalifah Muhammadun; A. Rio Makkulau Wahyu (MARGIN ECO, 2026)
This study was motivated by the increasing use of social media, which influences consumer behavior, particularly through the role of influencers and the Fear of Missing Out (FOMO) phenomenon. The study aims to analyze the influence of influencers and FOMO on the purchase intent of MSME fashion products in Sidenreng Rappang Regency. The research method employed was a quantitative approach using an associative research design. The research sample consisted of 99 respondents selected using purposive sampling. Data collection was conducted via a questionnaire using a Likert scale. Data analysis techniques included validity and reliability tests, classical assumptions, and multiple linear regression using SPSS. The results indicate that influencers and FOMO have a positive and significant effect on purchase intent, both partially and simultaneously. The coefficient of determination (Adjusted R-squared) value of 0.654 indicates that 65.4% of the variation in purchase interest can be explained by these two variables. Thus, marketing strategies based on influencers and FOMO are effective in increasing consumer purchase interest.